Business information systems 11th International Conference, BIS 2008, Innsbruck, Austria, May 5-7, 2008, Proceedings - International Conference on Business Information Systems |n |d 2008 : |c Innsbruck, Austria) (Lecture notes in business information processing, 2008)
This book contains the refereed proceedings of the 11th International Conference on Business Information Systems, BIS 2008, held in Innsbruck, Austria, in May 2008. The 41 revised full papers were carefully reviewed and selected for inclusion in the book. The contributions cover research trends as well as current achievements and cutting edge developments in the area of modern business information systems. They are grouped in sections on business process management, service discovery and composition, ontologies, information retrieval, enterprise resource planning, interoperability, mobility and contexts, wikis and folksonomies, and rules and semantic queries. Information retrieval -- An entry vocabulary module for a political science test collection -- Chinese organization entity recognition and association on web pages -- Language model based temporal information indexing -- Wikis and folksonomies -- Turning a corporate Folksonomy into a lightweight corporate ontology -- Discovering semantics in multimedia content using wikipedia -- Combining structure and semantics for ontology-based corporate wikis -- Ontology development -- Agreeing while disagreeing, a best practice for business ontology development -- Modeling and using polish legal knowledge - Commercial companies code ontology -- A supply chain management approach to logistics ontologies in information systems -- Ontology application -- Transforming existing knowledge models to information extraction ontologies -- Community-driven ontology evolution: gene ontology case study -- Semantic integration of process models into knowledge management: a social tagging approach -- BPM: modelling -- Influence factors of understanding business process models -- Concepts for modeling hybrid products in the construction industry -- Improving requirements analysis through business process modelling: a participative approach -- BPM: towards flexibility -- Weak dependencies in business process models -- Advanced querying and reasoning on business process models -- Prototypical implementation of a pragmatic approach to semantic web service discovery during process execution -- BPM: monitoring and verification -- SAF: strategic alignment framework for monitoring organizations -- Towards measuring key performance indicators of semantic business processes -- Structural detection of deadlocks in business process models -- BPM: involving people -- Employee competencies for business process management -- Enterprise web services and elements of human interactions -- Specifying separation of duty constraints in BPEL4 people processes -- Service discovery and composition -- Web service discovery in the FUSION semantic registry -- Towards the aggregation of security requirements in cross-organisational service compositions -- Industrialized generation of financial services by component-based information systems -- Interoperability -- Making the agent technology ready for web-based information systems -- An architecture for a QoS-aware application integration middleware -- Performance and architecture modeling of interoperability system for SME’s -- ERP: analyses -- Measurement of business process orientation in transitional organizations: an empirical study -- A metric for ERP complexity -- Data and information quality assessment in information manufacturing systems -- ERP: international experiences -- A comparative study of enterprise system implementations in large north american corporations -- Enterprise resource planning (ERP) systems implementation challenges: a kenyan case study -- Web data integration system: approach and case study -- Rules and semantic queries -- Integration of data and rules in inference with queries method -- Semantically sensitive execution of relational queries -- From business rules to application rules in rich internet applications -- Mobility and contexts -- Enabling context-based cooperation: a generic context model and management system -- Hydra – An application framework for the development of context-aware mobile services.